Movement on the Edge of Cities: Analysing Intra-urban Mobility in Peri-urban Communities in Southwest Nigeria - Yakubu, Samuel; Samuel, Kayode; Kola-Olusanya, Anthony; Yakubu, Deborah Ayodele; Adedotun, Samuel Babatunde (Bulletin of Geography. Socio-economic Series, 2023)
Mobility plays a crucial role in joining activity’s locations to each other, enabling social contact, and facilitating the movement of people and goods from and to various locations. This study investigates the mobility characteristics of peri-urban communities in selected cities of Southwest Nigeria. We selected 505 respondents from the 11 peri-urban communities for the questionnaire survey using a stratified sampling technique. The data were summarised using frequency, mean and mode while ANOVA and Chi-square were used to test for the significant difference in inter-community and gender variations in mobility variables. Findings revealed a substantial variation in the distance separating the peri-urban communities and the city centres. Most of the respondents (81.4%) indicated that the roads in their communities were not paved, with adverse effects on their mobility. The peri-urban communities are served by informal transit modes, with more than 33% of the respondents relying on motorcycles for their mobility needs. Mobility characteristics among the peri-urban dwellers vary from one community to another and between gender. Over 80% of respondents work within the peri-urban interface, indicating increasing decentralisation of activities. The peri-urban dwellers are mobility-starved due to failed infrastructure and informal transit services. The government at all levels (Federal, State and Local) should prioritise improving road infrastructures and public transport services that enhance sustainable mobility at the city peripheries.